Development of Modified Duty Cycle Technique to Enhance the Effectiveness of DC-DC Boost Converter - Wiryajati, I Ketut; Putra, I Ketut Perdana; Adnyani, Ida Ayu Sri (Teknik Elektro Universitas Siliwangi, 2025)
The DC-DC boost converter is a crucial component in power management systems, functioning to step up the DC voltage from a lower to a higher level. However, the effectiveness of the converter is often hindered by power losses and suboptimal efficiency. This study presents a performance analysis of three control methods applied to the Boost Converter: Conventional PWM, PWM with Modified Duty Cycle Switching (MDCS), and a Proportional-Integral (PI) Controller. Simulation results indicate that the Conventional PWM method exhibits low efficiency (88%) along with significant overshoot and steady-state error. The MDCS method demonstrates improved efficiency (91.7%) and a faster response time; however, it tends to experience substantial voltage fluctuations, indicating instability during transient conditions. In contrast, the PI controller delivers the most optimal performance, achieving the highest efficiency (94%) and a stable output voltage without significant fluctuations. The PI technique effectively maintains the reference voltage with minimal steady-state error and overshoot, making it an ideal solution for applications requiring high stability and efficiency. In conclusion, the PI controller is recommended for power conversion applications that demand stability, while the MDCS method is more suitable for systems requiring fast response with consideration for stability. The Conventional PWM method should be avoided in applications that require high efficiency